Algal polycultures enhance coproduct recycling from hydrothermal liquefaction. (January 2017) - Godwin, Casey M.; Hietala, David C.; Lashaway, Aubrey R.; Narwani, Anita; Savage, Phillip E.; Cardinale, Bradley J.
Graphical abstract: Highlights: Monocultures of algae were killed or inhibited by addition of 1–2% ACP. Polycultures of 2–6 species of algae responded positively, up to 10% ACP. Most polycultures exhibited increased growth rate and biomass production with ACP. Polycultures could overcome inhibition by ACP and increase biomass production. Abstract: The aim of this study was to determine if polycultures of algae could enhance tolerance to aqueous-phase coproduct (ACP) from hydrothermal liquefaction (HTL) of algal biomass to produce biocrude. The growth of algal monocultures and polycultures was characterized across a range ACP concentrations and sources. All of the monocultures were either killed or inhibited by 2% ACP, but polycultures of the same species were viable at up to 10%. The addition of ACP increased the growth rate (up to 25%) and biomass production (53%) of polycultures, several of which were more productive in ACP than any monoculture was in the presence or absence of ACP. These results suggest that a cultivation process that applies biodiversity to nutrient recycling could produce more algae with less fertilizer consumption.